Empreendedorismo feminino: uma análise do perfil da mulher empreendedora na cidade de Parintins/AM - Batista, Sandra Márcia Baraúna (Brasil, 2024)
This study discusses the results obtained during a research carried out in 2022/2023, which deals with the female entrepreneurial reality in the city of Parintins. Female Entrepreneurship is an increasingly transformative reality in our country. Many women have managed their own businesses as a way of facing the economic reality in crisis and at the same time contributing to the financial independence of other women, as well as in the fight for equality and against prejudice and machismo in the business world. This study sought to investigate the profile of female entrepreneurs and the challenges of Female Entrepreneurship in Parintins. To this end, the research uses a Qualitative and Descriptive approach carried out through a Case Study, with 20 Entrepreneurs Investigated. To obtain the information necessary to understand the phenomenon, we chose to use Observation, Questionnaire and Interview as Research Techniques. From the information obtained in relation to the universe of women investigated, it is clear that the majority of them are single entrepreneurs aged between 35 and 54 years old with two or more children, with higher education in the area of Social and Exact Sciences, motivated to undertake due to the need to support their families. In relation to the challenges, these are mainly related to the lack of structure, marketing and prejudice.